Study on the Control Strategy of Flue Gas in the Combined Cycle Power Station under Low Load Conditions - Kai WANG; Yugang LI; Zhitan LIU; Bo WANG; Weiwei SHAO; Chen SUN (Zhongguo dianli)
The emission problem of yellow plume generally occurs at the combined cycle power plants where the heavy-duty gas turbines is installed and operated during the turbine start-up process or under low load conditions. It becomes even worse especially for those units actively participating the peak load regulation. It is found out that yellow plume is caused by the rising NO2 concentration in flue gas. In order to further understand the formation mechanism of yellow plume in gas turbines for the purpose of more effective control on the content of NO2 in flue gas under low load conditions, the authors took GE 6F.03 gas turbine as the research object and implemented the method of field flue gas testing by measuring the flue gas composition at different positions in the heat recovery steam generator (HRSG) at the start-up stage of gas turbine. Then the factors affecting yellow plume generation were analyzed and compared. Finally from the gas turbine side and the heat recovery steam generator (HRSG) side, the countermeasures and detailed control procedures for heavy gas turbine to suppress yellow plume are put forward.